Drug Treatment of Patients with Liver Cirrhosis in a Tertiary Hospital in Northern Ghana: Does It Comply with Recommended Guidelines? - Baba Sulemana Mohammed; Matthew Aidoo (International Journal of Hepatology)
The diverse influence of liver function on drug disposition can lead health-care practitioners to inappropriate drug selection, inappropriate drug dosing, or some level of therapeutic negativism. The aim of this study was to assess how drug prescribing in patients with liver cirrhosis at the Tamale Teaching Hospital comply with recommendations of pharmacotherapy and safety guidelines. A prospective cross-sectional study was conducted from February to July, 2019, at the medical ward of the Tamale Teaching Hospital. A total of 152 liver cirrhotic patients were included in this study. Common etiologies for liver cirrhosis were chronic hepatitis B 80 (52.6%) and chronic hepatitis C 30 (19.7%); about 12.5% of etiologies were unknown. Of the 1842 prescription issued, 69% (1270/1842) were compliant. Of the 572 noncompliant prescriptions, about 32% (183/572) were due to pharmacotherapy and 68% (389/572) due to safety guideline recommendations. There was a substantial number (31%) of prescription noncompliance with recommendations for pharmacotherapy and safety guidelines in liver cirrhotic patients at the tertiary hospital in northern Ghana. Prescribers need to be conscious of the role of the liver in drug elimination and prescribe as recommended by guidelines.